Tropical Legume Crop Rotation and Nitrogen Fertilizer Effects on Agronomic and Nitrogen Efficiency of Rice - Motior M. Rahman; Aminul M. Islam; Sofian M. Azirun; Amru N. Boyce (The Scientific World Journal)
Bush bean, long bean, mung bean, and winged bean plants were grown with N fertilizer at rates of 0, 2, 4, and 6 g N m−2 preceding rice planting. Concurrently, rice was grown with N fertilizer at rates of 0, 4, 8, and 12 g N m−2. No chemical fertilizer was used in the 2nd year of crop to estimate the nitrogen agronomic efficiency (NAE), nitrogen recovery efficiency (NRE), N uptake, and rice yield when legume crops were grown in rotation with rice. Rice after winged bean grown with N at the rate of 4 g N m−2 achieved significantly higher NRE, NAE, and N uptake in both years. Rice after winged bean grown without N fertilizer produced 13–23% higher grain yield than rice after fallow rotation with 8 g N m−2. The results revealed that rice after winged bean without fertilizer and rice after long bean with N fertilizer at the rate of 4 g N m−2 can produce rice yield equivalent to that of rice after fallow with N fertilizer at rates of 8 g N m−2. The NAE, NRE, and harvest index values for rice after winged bean or other legume crop rotation indicated a positive response for rice production without deteriorating soil fertility.